The Effects of an Unconditional Cash Transfer on Mental Health in the United States - Clemente Pignatti; Zachary Parolin (Institute of Labor Economics (IZA), 2023)
Mental health conditions have worsened in many countries in recent decades. The provision of unconditional cash transfers may be one effective policy strategy for improving mental health, but causal evidence on their efficacy is rare in high-income countries. This study investigates the mental health consequences of the 2021 Child Tax Credit (CTC) expansion, which temporarily provided unconditional and monthly cash support to most families with children in the United States (US). Using data from the Behavioral Risk Factor Surveillance System, the largest health-related survey in the US, we exploit differences in CTC benefit levels for households with younger versus older children. More generous CTC transfers are associated with a decrease in the number of reported bad mental health days. The effect materializes after the third monthly payment and disappears when the benefits are withdrawn. The CTC's improvement of mental health is larger for more credit-constrained individuals, including low-income households, women, and younger respondents.
Keywords: H51; I18; J18; 330; child tax credit; mental health; public policy